Language learning through retelling the reading-writing connection - Abello, Larcy C. (UP Los Baños Journal, 2008)
This paper presents a sample retelling of a traditional tale to engage and help students respond to literature and make the reading-writing connection. Retelling of stories modeled by the teacher can inspire critical thinking and sound decision-making among students as they attempt to write their retelling. The task can motivate students to choose stories, take a closer look at the text features, and offer new insights to the original material. Even if reading, modeling, interactive activities, and discussions in class are valuable, the teacher can go a bit further to broaden the students' choices, deepen their grasp, and sharpen their thoughts for their own writing. Thus, language learning becomes fruitful, fulfilling, meaningful and enjoyable. Both the teacher and students benefit from activity as they explore innovative ideas, connect reading and writing in the context of the story, and create versions of their own.